Rosyjska tożsamość narodowa wobec modernizacji literatury - Nakoneczny, Tomasz (Wydawnictwo-Drukarnia Bonami/Pracownia Komparatystyki Literackiej IFP UAM, 2007)
The author sets about the task of presenting selected aspects of modernisation of the contemporary Russian literature in the perspective of broader cultural and social phenomena. Modernisation, by reference to Jerzy Święch, is understood as a process of identity changes initiated by the 19th century modernism and presently realised as post-modernism. In his considerations of the development and nature of the said process the author underscores the role of the Russian intelligence as a social class responsible for its distortions. It concerns cultural imperialism whose most important manifestations are exposed on the grounds of contemporary postcolonial research. Russian post-modern literature is seen in the article as a realm in which traditional values of the Russian culture, such as e.g. its sensitivity to general truths, clash with more and more explicit tendencies to annul or adapt them to new circumstances in post-Soviet Russia.
Keywords: Modernizm; Postmodernizm; Rosyjska tożsamość narodowa; Rosyjska literatura; Literatura i tradycja imperialna; Koniec historii vs. rosyjski duch